Corrole and Porphyrin Amino Acid Conjugates: Synthesis and Physicochemical Properties. Issue 32 (29th June 2016) - Karikis, Kostas; Georgilis, Evangelos; Charalambidis, Georgios; Petrou, Athanasia; Vakuliuk, Olena; Chatziioannou, Theodore; Raptaki, Iliana; Tsovola, Sofia; Papakyriacou, Ioanna; Mitraki, Anna; Gryko, Daniel T.; Coutsolelos, Athanassios G.
Abstract: A series of conjugates of amino acids with porphyrins and corroles was synthesized. Their self‐assembling ability under defined conditions was investigated by scanning electron microscopy. The morphology and photophysical properties of these molecules were studied by absorption and fluorescence spectroscopy in solid, liquid, and self‐assembled forms. We observed that both corrole and porphyrin conjugated with thel ‐phenylalanine–l ‐phenylalanine peptide to form spherical nanostructures with bathochromic shifts in the emission spectra, indicating the formation of aggregates. These aggregates are characterized by the impressive absorption of light over nearly the whole visible range. The broadening of all bands was particularly strong in the case of corroles. The fluorescence lifetimes of self‐assembled species were longer as compared to the solid‐state form. Abstract : It′s a round‐up : A series of conjugates of amino acids with porphyrins and corroles was synthesized (see figure). Their self‐assembling ability under defined conditions was investigated by scanning electron microscopy and their morphology and photophysical properties were analyzed by absorption and fluorescence spectroscopy in solid, liquid, and self‐assembled forms.